Effects of iron and calcium carbonate on the variation and cycling of carbon source in integrated wastewater treatments. (February 2017) - Zhimiao, Zhao; Xinshan, Song; Yufeng, Zhao; Yanping, Xiao; Yuhui, Wang; Junfeng, Wang; Denghua, Yan
Graphical abstract: Highlights: Dead algae as carbon source promoted microorganism activity in denitrification. Optimal dosage of Fe ion improved the removal performance. AP-CW realized optimal removals with 100 μM Fe 3+, 50 μM iron and 0.2 mg/L CaCO3 . Abstract: Iron and calcium carbonate were added in wastewater treatments as the adjusting agents to improve the contaminant removal performance and regulate the variation of carbon source in integrated treatments. At different temperatures, the addition of the adjusting agents obviously improved the nitrogen and phosphorous removals. TN and TP removals were respectively increased by 29.41% and 23.83% in AC-100 treatment under 1-day HRT. Carbon source from dead algae was supplied as green microbial carbon source and Fe 2+ was supplied as carbon source surrogate. COD concentration was increased to 30 mg/L and above, so the problem of the shortage of carbon source was solved. Dead algae and Fe 2+ as carbon source supplement or surrogate played significant role, which was proved by microbial community analysis. According to the denitrification performance in the treatments, dead algae as green microbial carbon source combined with iron and calcium carbonate was the optimal supplement carbon source in wastewater treatment.